Comportamiento productivo de conejos nueva zelanda (Oryctolagus cuniculus L) alimentados con forrajeras tropicales - Buste Castro, Franklin Antonio (2012)
This research was executed at the experimental farm "La Maria", Faculty of Animal Science, UTEQ property, located 7.5 km road Quevedo - Mocache, province of Los Ríos. The investigation lasted 56 days. They pursued the following objectives: a) Determine the tropical forage parameters allowing for increased food production in New Zealand rabbits (caraca, mulberry and xiv Buttercup) b) Determine the profitability of the treatments. 32 rabbits were used unsexed New Zealander, 35 days old, with an average weight of 493.16 g. We used a completely randomized design (CRD) with four treatments, four replications and two animals per experimental unit. To establish the differences between treatments means was applied multiple range test of Tukey (P ≤ 0.05). The yield was obtained, through the benefit - cost ratio. Consumption was assessed: fodder balanced; food (farraje + balanced) live weight gain weight feed conversion, weight and carcass yield. The higher forage intake (P <0.01) was registered based treatment mulberry (46.69 g DM animal-1 day-1). Similarly this record the greatest forage feed intake (90.76 g DM animal-1 day-1), live weight (1943.63 g), weight gain (26.91 g animal-1 day-1) but unregistered statistical differences (P> 0.05). Treatments based mulberry caraca reported the greatest weight, carcass yield and profitability (1068.00 to 1052.75 g and 54.92 to 55.20%, from 22.14 to 22.92%, respectively). The results allowed us to demonstrate that with the use of local feed resources of adequate nutritional quality, satisfactory results are obtained in fattening rabbits. Keywords: Food, forage, legumes, fodder, shrubs.